(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Reusing dialyzers to reduce costs is common in developing country. Resusing decreases dialysis efficiency, affects quality of life and increases the mortality. Therefore, evaluation of dialysis efficiency is necessary. Nephrologists in different countries use two indices, URR and Kt/V, to evaluate the effectiveness of dialysis, according to KDOQI recommendations, a minimum dose of Kt/V≥1.2 and URR≥65%. Objectives: To evaluate the efficiency of dialysis at Thong Nhat Dong Nai general hospital by using the Kt/V and URR indices and the relationship between the two indices Kt/V and URR with the number of times that the dialyzers is reused. Research methods: Cross-sectional descriptive study on 152 dialysis sessions of 152 patients on stable cycle dialysis who met the inclusion criteria. The dialysis sessions were divided into 3 independent groups. Group 1 used the totally new dialyzer; Group 2 used the third reused dialyzer; Group 3 used the 6th reused dialyzer. The patients used the same type of Nikkiso dialyzer, that had volume 1.5 m2, Triacetate material and the same type of dialyzer washing machine. The patients were taken blood for urea test before and after dialysis, recorded weight, ultrafiltration volume, time of 3.5 hours and blood pumping speed of 220-230 ml/min. Research results: Age group 40-60 accounts for the proportion of 48.1%, normal BMI (70.4%), dialysis time < 5 years (63.8%, male / female ratio = 1, 1. Overall, over 152 dialysis sessions, the Average URR Index was 67.36 ± 6.46 and Kt/V was 1.34 ± 0.2, 62.5% of dialysis sessions had URR meeting the recommendations; 69.1% of dialysis sessions had Kt/V meeting recommendations. There was a statistically significant difference in dialysis efficiency based on URR (Group 1, 73.3% of dialysis sessions had URR met; group 2, 68.9% of dialysis sessions had a satisfactory URR; in group 3, 50.8% of dialysis sessions had a satisfactory URR. The difference was statistically significant in dialysis efficiency calculated by kt/V. (Group 1, 53.3% of dialysis sessions had satisfactory Kt/V; group 2, 45.9% of dialysis sessions had satisfactory Kt/V; group 3, 21.3% of dialysis sessions had satisfactory Kt/V). There was a statistically significant difference in dialysis efficiency calculated in terms of URR and average Kt/V between the 3 groups using dialyzers again, with p < 0.05. Dialysis sessions efficiency tends to decrease gradually. Conclusion: Average URR is 67.36 ± 6.46 and Kt/V is 1.34 ± 0.23. Overall, 62.5% of dialysis sessions had URRs that met recommendations; 69.1% of dialysis sessions had Kt/V meeting recommendations. Urea and Kt/V indexes gradually decrease with the number of times the dialyzer was reused. Reusing dialyzer for the 6th time, the dialysis sessions efficiency decreased significantly.